Qualidade dos frutos de sete genótipos de abacaxizeiro - Cunha, Joilton Tavares (2013)
The pineapple shows a market that moves annually about US$ 1 billion, is grown in over 50 countries, with Brazil being the world's second largest producer. The expansion of thismarket is directly related to the production of high quality fruit, which requires efforts of researchers in the pursuit of superior genotypes that delight the consumer by the taste, aroma, integrity and nutritional value of pulp. This study characterized the pulpof different genotypes of pineapple ('Smooth Cayenne', 'Pérola', 'Vitória', EC-117, EC-118, EC-119 and EC-122)with the aim of assisting the selection of promising hybrids and categorizescultivars already established in the market. Fruitswere analyzed as the composition of sugars, acidity,humidity pulp, mineral elements profile, pulp total antioxidant capacity by ABTS and DPPH methods, total phenolic, flavonoid and ascorbic acid. The fruits of cv. Vitória stood out by higher levels of potassium and iron, the largeamount of sugars and the more concentrated pulp. Were observed in cv. Pérolaand hybrid EC-119 fruit with low acidity and high antioxidantpotential, however, cv. Pérolaproved to be the most nutritionally poor. The study characterized the volatile compounds of three genotypes already in the market, 'Vitória', 'Pérola' and 'Smooth Cayenne' and found that the fruits have similar aromas (over 40 compounds)and cv. Pérola, a higher concentration of citrus notes. Together, the study evaluated characteristics associated with internal browningin this genotipes. 'Victory' and 'Smooth Cayenne' showed the highest potential to be susceptible to internal browning since it had the lowest concentrations of ascorbic acid and sulfur and, consequently, lower activity of polyphenol oxidaseand peroxidase. Thus, it was evidenced that among the seven genotypes, cv. Vitória stands by taste and wealth of minerals in the pulp, although it requires greater care to prevent browning and cv. Pérolaeven more resistant to browning, is poor in minerals and has low sweetnesspotential.